Manajemen Pembelajaran Tematik Berbasis Karakter Di SD Negeri 2 Tanjungharjo Kecamatan Ngaringan - Ervianto, Idih Dwi, Dr. Maryadi, M.A, Dr. Anam Sutopo, M.Hum (2017)
This research aims to know the preparation 1) thematic character-based curriculum in SD Negeri 2 Tanjungharjo 2) know the preparation of educators in pursuing a thematic character-based learning in SD Negeri 2 Tanjungharjo. 3) do know the implementation of thematic character-based learning in SD Negeri 2 Tanjungharjo. 4) knowing the character-based thematic curriculum evaluation in SD Negeri 2 Tanjungharjo. This research was conducted by using a qualitative approach. The data in this research in the form of words and the results of the interview are transliterated from a recording using the tool in the form of tape recorders or other electronic recording device that can be used as a means of visual or sound recorder. As for steps data analysis include: data collection, data Presentation, data Reduction, and the withdrawal of the conclusion. The results showed: 1) preparation of thematic character-based curriculum in SD Negeri 2 Tanjungharjo in the form of data, process, the syllabus and the RPP is structured by the teacher, which consists of 9 themes. 2) Preparation of educators in pursuing a thematic character-based learning in SD Negeri 2 Tanjungharjo consists of 10 teachers. 3) implementation of thematic characterbased learning in SD Negeri 2 Tanjungharjo committed teachers in implementing the learning, i.e., learning strategies, learning Media, methods of teaching and learning Evaluation. 4) thematic character-based curriculum Evaluation in SD Negeri 2 Tanjungharjo has been carried out properly, the next teacher evaluation in order to carry out the planned its realization is known already to meet expectations in accordance with the intended purpose. The implementation of an evaluation study has appropriate preparation for learning (syllabus, RPP) and evaluation steps of learning that is planning an evaluation, implementation evaluation, evaluation of results, data processing and reporting evaluation results evaluation. In addition, with the evaluation of the teacher can find out the model of learning that is planned and used already right on target or not